Treatment Complexities of a Young Woman Suffering Psychosis and Pituitary Adenoma - Sigman, Maxine; Drury, Kate (Case Reports in Psychiatry, 2011)
This paper is a clinical description of the presentation, therapy, and pharmacological management of a 28-year-old woman who had nine admissions to a psychiatry ward, the last four within one year. It became clear that the treatments, which the patient had received concurrently for ten years for a pituitary adenoma and for psychotic symptoms, were counteractive. The case highlights the importance of the role of prolactin in psychosis and of an interdisciplinary team approach when patients present with complex symptoms.